Thomas More’s Portrayal in a Twentieth-Century Translation of Utopia - Ureña-Asensio, María Inmaculada (The Grove - Working Papers on English Studies, 2021)
Ramón Esquerra i Clivillés (1909-1938), a Spanish intellectual born and raised in Barcelona, published in 1937 Utopia (El Estado Perfecto), a translation of Utopia (1516) by Thomas More. The translator prepared a large prologue in which he minutely details the life and personality of the humanist and introduces Utopia and its reception in Spain. As a result, this illuminating introductory section becomes a brief piece of literary criticism. The way More is presented and how Esquerra emphasizes some of his most personal features creates a particular image of the humanist: that of a saint. The information shown was carefully chosen by the translator, serving from of More’s latest published biographies to construct a useful context for the reader.